Theoretical Study on Horizontal-Type SAW Device with Dual Function of Sensing and Removal of Non-specific Binding - Chen, C.; Wang, Y.; Ao, T.; Hui, G. (Acta Physica Polonica A, 2024)
In this paper, a horizontal-type surface acoustic wave device based on electrode width control interdigital transducer/polymethylmethacrylate/54° Y–X LiNbO3 is proposed to achieve the removal of non-specific binding particles by Rayleigh waves and the detection of meningococcus by Love waves. It is proved that the surface acoustic wave force plays a leading role in the removal of non-specific binding,  and  the  frequency  of  the  acoustic  wave  also  affects  the  removal  effect. The advantage of electrode width control interdigital transducer lies not only in overcoming the shortcomings of bidirectional and focused interdigital transducers, but also in improving  the  utilization  of  acoustic  waves  and  the  sensitivity  of  the  sensor. When non-specific binding particles are removed by Rayleigh  waves,  the  Love  wave  sensor  shows  a sensitivity of 330 Hz/(ng/µL) and a detection limit of 50 pg/µL for meningococcus.